analysis of the flash cards use in the lexis learning in the process of teaching english as a foreing language at the initial ii of parallel a at combatientes de tapi high school, in the city of riobamba, during the quimester school period 2017-2018. - Amán Cauja, Gabriela Alexandra (2018)
This research focuses on analysing the use of flashcards as a strategy to introduce new vocabulary in the process of teaching English as a foreign language, with students at Initial II class “A” At Unidad Educativa “Combatientes De Tapi”. The study is framed in the qualitative approach due to it carried out an observation process to describe the use of flashcards, as a didactic material to teach vocabulary. The ethnographic method and the direct observation technique were used to gather the necessary information to develop the research. The results evidenced that the words presented are easy enough for the students, so the little kinds can effortlessly catch them; but at the same time they presented in isolation, it means that there is not any connection of the new word with its use in extracurricular contexts, the flashcards are completely done by the teacher without the students´ participation. It is recommended for the teacher to identify the strategies that best fits the students’ age, level, interest and needs, and modify or adapt them to their social and educational reality.